Beseda s Prezidentom respubliki Kalmykiia Kirsanom Iliumzhinovym . Beseda s Prezidentom respubliki Kalmykiia Kirsanom Iliumzhinovym . Interview with the President of the Republic of Kalmykia, Kirsan Ilyumzhinov . Беседа с Президентом республики Калмыкия Кирсаном Илюмжиновым - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with the President of the Republic of Kalmykia. Featured in the program: Iliumzhinov, Kirsan Nikolaevich (President of the Republic of Kalmykia) Contributors: Shishov, Aleksei (Anchor) Беседа с президентом республики Калмыкия. В программе участвуют: Илюмжинов, Кирсан Николаевич (Президент Республики Калмыкия) Создатели: Шишов, Алексей (Ведущий/Ведущая)